Molecular and morphological analyses clarify species delimitation in section Costatae and reveal Betula buggsii sp. nov. (sect. Costatae, Betulaceae) in China. (8th January 2022) - Wang, Luwei; Ding, Junyi; Borrell, James S; Cheek, Martin; McAllister, Hugh A; Wang, Feifei; Liu, Lu; Zhang, Huayu; Zhang, Qiufeng; Wang, Yiming; Wang, Nian
Abstract: Background and Aims: Delineating closely related and morphologically similar species is difficult. Here, we integrate morphology, genetics, ploidy and geography to resolve species and subspecies boundaries in four trees of section Costatae (genus Betula ): Betula ashburneri, B. costata, B. ermanii and B. utilis, as well as multiple subspecies and polyploid races. Methods: We genotyped 371 individuals (20–133 per species) from 51 populations at 15 microsatellite markers, as well as a subset of individuals, using restriction-site associated DNA sequencing and nuclear internal transcribed spacers. We determined the ploidy level of eight individuals using flow cytometry and characterized leaf variation for a subset of 109 individuals by morphometric analysis. Key Results: Integration of multiple lines of evidence suggested a series of revisions to the taxonomy of section Costatae . Betula costata and B. ermanii were found to be valid. Molecular and leaf morphology analyses revealed little differentiation between diploid B. albosinensis and some samples of B. utilis ssp. utilis . By contrast, other B. utilis ssp. utilis samples and ssp. albosinensis formed a morphological continuum but differed based on genetics. Specifically, B. utilis ssp. albosinensis was divided into two groups with group I genetically similar to B. utilis ssp. utilis and group II, a distinct cluster, proposed as the new diploid species Betula buggsii sp. nov. Phylogenomic analysis based on 2285 620 single nucleotide polymorphisms identified a well-supported monophyletic clade of B. buggsii . Morphologically, B. buggsii is characterized by elongated lenticels and a distinct pattern of bark peeling and may be geographically restricted to the Qinling–Daba Mountains. Conclusions: Our integrated approach identifies six taxa within section Costatae : B. ashburneri, B. buggsii, B. costata, B. utilis ssp. utilis, B. utilis ssp. albosinensis and B. ermanii . Our research demonstrates the value of an integrative approach using morphological, geographical, genetic and ploidy-level data for species delineation.